The validity and reliability of wearable microtechnology for intermittent team sports: A systematic review - Crang, Z. L.; Duthie, G.; Cole, M. H.; Weakley, J.; Hewitt, A.; Johnston, R. D. (Sports Medicine, 2021)
Background: Technology has long been used to track player movements in team sports, with initial tracking via manual coding of video footage. Since then, wearable microtechnology in the form of global and local positioning systems has provided a less labour-intensive way of monitoring movements. As such, there has been a proliferation in research pertaining to these devices.